Convenient One-Pot Synthesis of Spirooxindole Derivatives Containing a 1,3,4-Thiadiazine Scaffold - Alizadeh, Abdolali; Moafi, Leila (Synlett, 2016)
A useful strategy for the construction of spirocyclic oxindoles bearing a 1,3,4-thiadiazine skeleton is reported. The desired products were obtained in high yields under mild conditions.
Keywords: spiro compounds; heterocycles; indoles; thiadiazines; cyclizations